Low-Dose-Rate Brachytherapy Boosting Concurrent Chemoradiation as a Definitive Treatment Modality for Cervical Cancer: Long-term Clinical Results of Outcomes and Associated Toxicity. (April 2016) - Refaat, Tamer; Donnelly, Eric D.; Gentile, Michelle; Novak, Caroline; Yuan, Ye; Khedr, Gehan A.; Helenowksi, Irene; Lurain, John; Schink, Julian; Rademaker, Alfred; Sathiaseelan, Vythialinga; Strauss, Jonathan B.; et al.
Abstract : Purpose: To review and report the long-term treatment-induced adverse events (AEs) and outcomes of concomitant chemoradiotherapy boosted by low-dose-rate (LDR) conventional brachytherapy (BT) planning in patients with locoregionally advanced cervical cancer. Patients and Methods: After obtaining institutional review board approval, we reviewed the records of patients with stage IB1 to IVA, intact cervical cancer who were treated at our institution between 1983 and 2009. Eligible patients underwent definitive radiotherapy with external-beam radiation concomitant with cisplatin-based chemotherapy and boosted by LDR BT. Patient, tumor, and treatment characteristics; treatment-induced AEs, namely, gastrointestinal and genitourinary toxicities, as well as treatment outcomes; locoregional control (LRC), distant control (DC), progression-free survival (PFS), and overall survival (OS) were reviewed and reported. Results: The study included 129 eligible cervical cancer patients; the median age was 46 years (mean, 47±11 y; range, 28 to 81 y), consisting of stages I, II, III, and IV (29.5%, 48.1%, 17.8%, and 4.6%, respectively). The median follow-up was 37 months (mean, 58±59 mo; range, 3 to 275 mo). The 3-year OS, PFS, LRC, and DC were 75.9%, 71.6%, 84.7%, and 80.2%, respectively. The 5-year OS, PFS, LRC, and DC were 70.7%, 68.7%, 84.7%, and 78.3%, respectively. The 10-year OS, PFS, LRC, and DC were 68.7%, 62.3%, 82.5%, and 73.2%, respectively. Gastrointestinal and genitourinary grade 3 and 4 acute AEs were reported in 3.9% and 0%, and chronic grade 3 and 4 AEs were reported in 20.9% and 12.4% of all patients, respectively. Conclusions: Definitive chemoradiotherapy followed by conventional LDR BT boost is effective, feasible, and tolerable treatment modality for cervical cancer. A comparison with MRI image-guided BT shows comparable treatment outcomes with superior OS in favor of LDR BT but inferior LC with a relatively worse toxicity profile.